Analysis of the wake mechanism in external flow around tandem bluff bodies with different aspect ratios - Abbasi, Waqas Sarwar; Ehsan, Muhammad; Rahman, Hamid; Uddin, Zia; Hassan, Mohammad Mehedi; Saleem, Kashif (Frontiers in Mechanical Engineering, 2024)
The interaction mechanism of external flow with two inline rectangular cylinders having different aspect ratios under the impact of gap spacing (G) is the subject of this research. The gap spacing between the cylinders was varied from 0.25 to 20 times their size. Both cylinders were vertically mounted, with the first having a higher aspect ratio than the second. The results revealed five distinct flow patterns under the influence of G: single slender body, shear layer reattachment, intermittent shedding, binary vortex street, and single-row vortex street. The mean pressure on both cylinders was found to vary due to changes in flow patterns. Both cylinders bore the same shedding frequency but had different pressure variations. The second cylinder placed in the wake of first experienced negative average drag force for some spacing values, while the first cylinder had positive average drag values for all chosen G. Due to the change in flow pattern from shear layer reattachment to intermittent shedding flow, the negative drag force on the second cylinder jumped to a positive drag. It was also observed that the rms values of drag and lift force coefficients, as well as their amplitudes for the second cylinder, were mostly higher than corresponding values for the first cylinder at all selected G. This study revealed that G = 4 and 8 are the critical gap spacing values due to sudden changes in fluid force parameters.